Nitric oxide-donor SNAP induces Xenopus eggs activation - Jeseta, Michal; Marin, Matthieu; Tichovska, Hana; Melicharova, Petra; Cailliau-Maggio, Katia; Martoriati, Alain; Lescuyer-Rousseau, Arlette; Beaujois, Rémy; Petr, Jaroslav; Sedmikova, Marketa; Bodart, Jean-François (PloS one, 2012)
Nitric oxide (NO) is identified as a signaling molecule involved in many cellular or physiological functions including meiotic maturation and parthenogenetic activation of mammalian oocytes. We observed that nitric oxide donor SNAP was potent to induce parthenogenetic activation in Xenopus eggs. NO-scavenger CPTIO impaired the effects of SNAP, providing evidence for the effects of the latter to be specific upon NO release. In Xenopus eggs, SNAP treatment induced pigment rearrangement, pronucleus formation and exocytosis of cortical granules. At a biochemical level, SNAP exposure lead to MAPK and Rsk inactivation within 30 minutes whereas MPF remained active, in contrast to calcium ionophore control where MPF activity dropped rapidly. MAPK inactivation could be correlated to pronuclear envelope reformation observed. In SNAP-treated eggs, a strong increase in intracellular calcium level was observed. NO effects were impaired in calcium-free or calcium limited medium, suggesting that that parthenogenetic activation of Xenopus oocytes with a NO donor was mainly calcium-dependent.
Keywords: Kinetics; Xenopus laevis; kinetika; partenogeneze; Ovum; Parthenogenesis; oxid dusnatý; benzoáty; Imidazoles; donory oxidu dusnatého; vápník; Enzyme Activation; Animals; Calcium; Maturation-Promoting Factor; aparát dělícího vřeténka; Progesterone; Benzoates; zvířata; S-Nitroso-N-Acetylpenicillamine; ovum; faktor podporující zrání; imidazoly; morfogeneze; Spindle Apparatus; Nitric Oxide Donors; mitogenem aktivované proteinkinasy; aktivace enzymů; ženské pohlaví; Female; Nitric Oxide; S-nitroso-N-acetylpenicilamin; Mitogen-Activated Protein Kinases; progesteron; Morphogenesis